Three new species of Chloropidae (Diptera) from southern Sardinia - Nartshuk, Emilia P. (Zootaxa, 2009)
During a recent survey of arthropod diversity in several localities of southern Sardinia, three new species of Chloropidae (Diptera) were discovered: Aphanotrigonum lanceolatum sp. nov., Dicraeus sardous sp. nov. and Elachiptera sarda sp. nov. The first is close to A. hastatum Dely-Draskovits from Afghanistan; the second is placed in subgenus Oedesiella Becker; the third is compared to E. cornuta (Fallén, 1820) and E. rufifrons Duda, 1932.